2009
DOI: 10.1111/j.1442-2042.2009.02291.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related pain and quality of life in prostate cancer patients: Assessment using the Functional Assessment of Prostate Cancer Therapy

Abstract: Abstract:The objective of this study was to assess disease-associated pain and quality of life (QOL) in patients with prostate cancer (PC). A total of 102 PC patients (clinical stage B, C: 20, D2: 82) patients were enrolled. QOL was assessed using the Functional Assessment of Cancer Therapy, General and Prostate (FACT-G/P). Disease-specific pain response was assessed using the visual analog scale and the face rating scale. In patients with stage D2 PC, mean age, serum prostate-specific antigen level, and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…However, similarly high scores have been reported for Caucasian men 24 months post-diagnosis who received either radical prostatectomy or external beam radiation therapy (FACT-P mean = 128, SD = 17.1) [18]; and in Japanese patients treated with carbon ion therapy 12 months after treatment (FACT-P mean = 120.4 (SD = 21.1) [19]. Our sample showed similar variability to that reported in other studies [20][21][22].…”
Section: Discussionsupporting
confidence: 87%
“…However, similarly high scores have been reported for Caucasian men 24 months post-diagnosis who received either radical prostatectomy or external beam radiation therapy (FACT-P mean = 128, SD = 17.1) [18]; and in Japanese patients treated with carbon ion therapy 12 months after treatment (FACT-P mean = 120.4 (SD = 21.1) [19]. Our sample showed similar variability to that reported in other studies [20][21][22].…”
Section: Discussionsupporting
confidence: 87%
“…Fujimura et al. (), who focused on people with prostate cancer in Japan, found that people at the D2 stage of cancer had worse physical well‐being compared with those people at the B/C cancer stage, but they displayed no significant differences in emotional or social well‐being. The differences between these findings and those of the present study might be related to the different tracking periods of the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Control of disease-associated pain is crucial to improve HRQoL in mCRPC. A recent small trial has proved that performance status, extent of disease, and the visual analog scale (VAS) were related with a poor HRQoL score [6]. Psychological factors that may alter pain perception in patients with cancer could have a potential role in pain control [21].…”
Section: Symptom Burden Treatments and Hrqol Domains In Mcrpcmentioning
confidence: 99%
“…A recent small trial documented that performance status, extent of disease, and the VAS for pain assessment were related with a poor HRQoL score reported by FACT-P (physical and functional well-being, FACT-P total score). In particular, 32 patients (39%) had disease-specific pain and patients under morphine analgesics maintained higher HRQoL in almost all domains [6].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation